2011
DOI: 10.3324/haematol.2010.026740
|View full text |Cite
|
Sign up to set email alerts
|

Differential modulation of adhesion molecule expression by hydroxycarbamide in human endothelial cells from the micro- and macrocirculation: potential implications in sickle cell disease vasoocclusive events

Abstract: BackgroundAll the cellular partners of the vascular system and especially endothelial cells are involved in the pathophysiology of the vasoocclusive crises associated with sickle cell disease. In sickle cell disease, circulating cells adhere abnormally to endothelial cells in a chronic pro-inflammatory context. Hydroxycarbamide is the only drug with demonstrated efficacy to reduce the frequency of vasoocclusive crises. Here, we investigated the effects of hydroxycarbamide and/or cytokines on the expression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
27
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 52 publications
0
27
0
Order By: Relevance
“…23 The expression profile of these cells is, therefore, not informative for the HbF response to HU in erythroid progenitor cells. Other studies on the effect of HU in SCD patients show decreased expression of adhesion molecules in vascular endothelial and red cells, [24][25] its stimulating effect on proinflammatory gene expression, 26 and several other pathways. [27][28] To our knowledge, none of these studies address the differential HU response in β-thalassemia.…”
Section: Introductionmentioning
confidence: 99%
“…23 The expression profile of these cells is, therefore, not informative for the HbF response to HU in erythroid progenitor cells. Other studies on the effect of HU in SCD patients show decreased expression of adhesion molecules in vascular endothelial and red cells, [24][25] its stimulating effect on proinflammatory gene expression, 26 and several other pathways. [27][28] To our knowledge, none of these studies address the differential HU response in β-thalassemia.…”
Section: Introductionmentioning
confidence: 99%
“…This could be supported by the observation that, in vitro, HC decreases the expression of VCAM-1, a paradigmal marker of endothelial cell activation, at the surface of endothelial cells in culture. 25 Alternatively, the decrease in MPs shed by endothelial cells in our treated children may reflect a lower injury of these cells indirectly mediated by HC through its overall inhibiting effect on RBC alterations and vaso-occlusion. Clearly further studies are warranted to clarify the HC-induced effect on both platelets and endothelial cells.…”
mentioning
confidence: 99%
“…19,20 HC also reduces the number of white cells, platelets and reticulocytes, each of them contributing to the SCA-associated vaso-occlusion and vascular injury. [21][22][23] Finally, it has been shown that HC-treatment modulates the expression of erythroid and endothelial adhesion receptors and decreases the abnormal activation status of polymorphonuclear neutrophils [24][25][26] in SCA children. Such observations have led to the hypothesis that HC could have additional cellular targets other than red blood cells.…”
mentioning
confidence: 99%
“…Cokic et al (19) showed that in vitro short exposure of endothelial cells to HC increases cAMP and cGMP (cyclic guanosine monophosphate) and induces nitric oxide (NO) production in a NO synthase-dependent manner. We showed that in vitro treatment of endothelial cells with HC leads to a decreased expression of vascular cell adhesion molecule-1 (VCAM-1) (20) and of the vasoconstrictor peptide endothelin-1, which is in accordance with the decreased levels of plasma endothelin-1 in HC-treated children (21,22).…”
mentioning
confidence: 61%